Solusi Ketimpangan Sosial tentang Gender dalam Al-Quran - Musthofa Musthofa (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2016)
Gender is a term used to describe the sex of male and female. In the view of the Quran there is gender inequality related to the rights, obligations and responsibilities. To find out the gender imbalance in the Quran and how to solve it in this paper uses the method of approach through Tafsir bil Iswaji, which is an explanation of the issue through a combination of intellect and the texts of the Quran as well as the statements of the experts associated with it. This type of research is the research library, with descriptive analysis. It is expected in this study to determine; (1) Male gender and female gender inequality occurs in terms of inheritance rights and rights as a witness. Inequality inheritance rights can be resolved by understanding the ideological awareness of the Qur’an and compliance. Inequality rights as a witness can be overcome with feminist awareness and anfeminist with principle of the Qur’an ideology and boundaris. (2) Male gender and female gender inequality has the obligation to pay the dowry and income are called liabilities inequality. Dowry payments and income inequality can be addressed by means of feminist awareness and anfeminist with principle of the Qur’an ideology. Payment of income inequality can be addressed through feminist and anfeminist of the Qur’an ideology. (3) Male gender and female gender inequality are on the responsibility of the so-called responsibility inequality. This inequality can be addressed by means of awareness division of roles and relationships boundaris.